AGRICULTURAL INPUTS USE FOR SUSTAINABLE DEVELOPMENT: THE INNOVATIVE COUNTRIES AND THE REPUBLIC OF SERBIA - Dimitrijević, Miloš S; Bošković, Nikola; Veselinović, Petar; Leković, Miljan (Economics of Agriculture, 2024)
Bearing in mind the increasingly pronounced world challenges such as the growth of population on the world, climate changes and pandemics, there is an increasing emphasis on healthy and safe food, as well as environmental protection. Organic production achieves the best ecological advantages compared to all other agricultural production methods. However, its application is limited due to lower yields, which requires increasing productivity. The aim of the paper is to differentiate between conventional and organic inputs (resources) and their impact on agricultural production, economic and sustainable development. Ordinary Least Square (OLS) panel regression did not show a significant difference between conventional and organic inputs for agricultural production, where it is only important to increase the amount of inputs for higher production, while the increase in total factor productivity of inputs has a positive impact on the economic and sustainable development of the observed countries.